2020
DOI: 10.3390/foods9121749
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Waxy (High Amylopectin) and High Protein Digestibility Traits in Sorghum on Injera Sourdough-Type Flatbread Sensory Characteristics

Abstract: Injera, an East African leavened sourdough fermented pancake has remarkable textural properties despite being made from non-wheat flours. However, teff flour, which produces the best quality injera, is expensive and limited in availability. The effects of waxy (high amylopectin) and high protein digestibility (HD) traits in sorghum on injera quality were studied. Eight white tan-plant sorghum lines expressing these traits in various combinations and three normal sorghum types were studied, with teff flour as r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…far more frequently than from any other source [ 10 ]. Sour tastes, smooth, moist, elastic, spongy feel, multiple “eyes” (bubbles), and a long shelf life are the indicators of quality injera [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…far more frequently than from any other source [ 10 ]. Sour tastes, smooth, moist, elastic, spongy feel, multiple “eyes” (bubbles), and a long shelf life are the indicators of quality injera [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Injera stress and strain over storage were determined using a 3‐point bending rig with an aluminum bar (5 mm wide and 90 mm long) mounted on a SHIMADZU EZ‐L texture analyzer, as described by Mezgebe et al (2020).…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, however, neither pH nor TA were affected by the waxy and HD traits (Supporting Information: Table S2), due to the fact that there was no significant correlation between these (Supporting Information: Table S3). The methods used to determine starch amylose and in vitro protein digestibility are provided in Mezgebe et al (2018Mezgebe et al ( , 2020.…”
Section: Injera Batter Ph and Tamentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, waxy sorghum is also widely used in the food processing industry [ 7 , 8 ]. Mezgebe et al found that the waxy sorghum powder had considerable potential in the production of gluten-free fermented flat cake products, it had good structure and function [ 9 ]. The Elhassan group found that waxy sorghum flour, with high protein digestibility, had better dough-like properties than non-waxy sorghum, with normal protein digestibility [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%